Perancangan pet furniture dengan sistem knockdown untuk rumah tinggal - Soetedjo, Alyssa Lorenza; Kusumarini, Yusita; Lumintan, William Vijadhammo (Institut Seni Indonesia Yogyakarta, 2024)
Having a pet is a hobby for some people to relieve stress or boredom, because their behavior is considered fun and attractive. Interaction between humans and pets occured in many areas in the house, caused positive psychological effects for their owners. However, the observation showed that not many owners pay attention to the facilities between humans and their pets. This caused a lack of place for interaction and a place to do activities in a relaxed and comfortable atmosphere. The design purpose is to help owners and pets do their activity together, and have a close relationship between each other. The design method is design thinking with the stages of understand, define, point of view, idea, prototype, test, and implement. The concept of this design is